Helminths from Seven Species of Lizards (Reptilia: Squamata) at the Cerrado of Mato Grosso do Sul State, Brazil - Avila, Robson W. [UNESP]; Souza, Franco L.; da Silva, Reinaldo J. [UNESP] (Helminthological Soc Washington, 2010)
Sixteen specimens representing 7 species of lizards (Hoplocercus spinosus, Ophiodes striatus, Polychrus acutirostris, Stenocercus caducus, Tropidurus guarani, Tropidurus itambere, and Tupinambis merianae) collected in the Cerrado biome at the Brazilian state Mato Grosso do Sul were examined for helminths. Nine species of nematodes were recovered from lizard hosts (Cruzia travassosi, Cyrtosomum sp., Diaphanocephalus galeatus, Gynaecometra bahiensis, Pharyngodon cesarpintoi, Physaloptera sp., Skrjabinellazia intermedia, Strongyluris oscari, and an unidentified species of nematode). Five new host records and 3 new locality records were reported.
Keywords: parasites; Nematoda; Sauria; neotropical; Brazil; South America